Cardiopulmonary Function Assessment in Children With Pulmonary Valve Stenosis - Teng, Li Yun; Tsai, Sen Wei; Hsiao, Chun Yuan; Sung, Wei Hung; Lin, Ko Long (Frontiers in Pediatrics, 2022)
Objective Pulmonary valve (PV) stenosis affects cardiac pulmonary function and exercise performance. A cardiopulmonary exercise test (CPET) combined with a transthoracic echocardiogram (TTE) can measure exercise performance, disease progression, and treatment effects. We assessed the exercise capacity in children with PV stenosis by conducting CPET and TTE. Methods From 2005 to 2021, 84 patients with PV stenosis aged 6-18 years were enrolled; 43 were treated with balloon pulmonary valvuloplasty(BPV) (Group A), and 41 received follow-up care (Group B), and their CPET and pulmonary function test results were compared with 84 healthy, matched individuals (Control). We also conducted TTE to compare the peak pulmonary artery pulse wave velocity and pulmonary valve(PV) area before and after catheterization and follow-up care. Results There were no significant differences among the CPET parameters of the patient groups and controls in anaerobic metabolic equivalent(MET) (group A: 6.44±0.58; group B: 6.28±0.47, control: 6.92±0.39, p=0.110), peak MET (group A: 9.32±0.74; group B: 9.13±0.63; control: 9.80±0.52, p=0.263), and heart rate recovery(group A:28.04±4.70; group B:26.44±3.43, control:26.10±2.42, p=0.718). No significant differences were found in the pulmonary functions between the three groups. The pulmonary artery pulse wave velocity significantly decreased after catheterization (3.97±1.50 vs. 1.95±0.94, p<0.0001), but not after follow-up care (1.67±0.77 vs. 1.75±0.66, p=0.129). The pulmonary vale area significantly improved in group A (0.89±0.71 vs. 1.16±0.58, p<0.0001), whereas only insignificant progression of PV stenosis was observed in group B (1.60±0.64 vs. 1.57±0.65, p=0.110). Conclusions Patients treated with BPV had a similar exercise capacity with that of patients under follow-up care and the healthy controls. Larger or multi-center studies should be conducted to confirm the physical fitness of pediatric patients with PV stenosis after management.